An analytical method for halon alternative selection in fire suppression systems design. Issue 3 (22nd January 2010) - Bertolini, Massimo; Vignali, Giuseppe
Cleanliness is the priority property of an active fire-extinguishing agent for protection of expensive electronic equipment and high value materials. Halon 1301 was considered the most suitable clean agent to ensure industrial fire safety because it leaves no residue and allows a high level of extinction efficiency and human safety, as with many other extinguishing media. However, over 15 years ago, several studies showed that this agent damages the atmospheric ozone layer and causes global warming. As law has ruled out halon agents, a variety of clean fire suppression alternatives has surfaced over the past decade, but none of these has become the 'perfect' halon substitute. In this paper the analytic hierarchy process (AHP) approach is proposed as a tool to select the best halon alternative for fire protection. A hierarchical structure comprising 19 criteria is reported here to illustrate the performance and characteristics of several halon alternatives in order to define the most suitable agent for different fire risk situations.